Influence of Digital Literacy, Customer Intimacy, and Brand Image on Competitive Advantage - Muhammad Dairobi; Anisah, Hastin Umi (Open Access Indonesia Journal of Social Sciences, 2024)
The rapid evolution of digital markets necessitates an in-depth understanding of factors influencing the competitive advantage of digital-based SMEs, particularly within the food and beverage sector of Palangka Raya City. This research aims to dissect the roles of digital literacy, customer intimacy, and brand image in shaping the competitive landscape for these businesses. Focusing on owners and managers, the study utilizes a non-probability purposive sampling technique, engaging 106 respondents through questionnaires. Analysis was conducted using the PLS-SEM method against a backdrop of diverse demographics, primarily female entrepreneurs aged 21 to 30 years with varied educational backgrounds, operating micro-businesses for 1 to 5 years. Contrary to expectations, digital literacy did not show a significant impact on competitive advantage, a finding that diverges from common digital strategy assumptions. In contrast, customer intimacy and brand image were positively correlated with increased competitive advantage, highlighting their importance in the digital domain for SMEs in Palangka Raya City. These insights stress the critical need for SMEs to cultivate strong customer relationships and a robust brand presence, overshadowing the direct effects of digital literacy skills. The findings suggest a strategic pivot towards customer-centric and brand-oriented practices could be more beneficial for SMEs aiming for competitive superiority in the digital era. This study underscores the nuanced dynamics of competitive advantage in digital-based SMEs, offering a foundational guide for future strategic orientations.